Early childhood caries, obesity and anthropometric measurements: Is there a relationship? - Rizzardi, Karina Ferreira; Crescente, Camila Lopes; Indiani, Claudia Maria dos Santos Pereira; Steiner-Oliveira, Carolina; Nobre-dos-Santos, Marinês; Parisotto, Thaís Manzano (Frontiers in Nutrition, 2022)
This brief research report explored the relationship among obesity, anthropometric measurements, and early childhood caries (ECC), in 3–5 years-old children. Three hundred and ninety-one Brazilian preschoolers were given anthropometric examinations for the assessment of general, peripheral, and central adiposity, by the following measures: body mass index (BMI), hip circumference, and waist circumference. Obesity status was determined by BMI according to WHO standards. Parent's age and BMI were assessed by questionnaire, and sucrose exposure was tracked by means of a food diary. For the assessment of ECC, dental examinations were performed according to modified WHO criteria. Also, the presence of dental biofilm in maxillary incisors was detected. A direct association between BMI and ECC was found in the bivariate analysis and the best possibility of logistic regression model showed that hip circumference (HC) values ≥62 centimeters (OR = 1.63; p = 0.033) jointly with the presence of dental biofilm (OR = 2.38; p = 0.000), children's ages ≥37 months (OR = 5.09; p = 0.012), and mothers younger than 35 years (OR = 1.96; p = 0.004) were significantly connected with ECC. In conclusion, peripheral adiposity (represented by HC) in young children was in fact associated with ECC. Thus, hip circumference might be a valuable tool for exploring the relationship between caries and obesity in the early years of life.